Kausalität in der Muʻtazilitischen Kosmologie : das Kitab al-muʼaththirāt wa-miftaḥ al-muşkilāt des Zayditen al-Ḥasan ar-Raṣṣāṣ. (st. 584/1188) - Thiele, Jan. (Islamic Philosophy, Theology and Science. Texts and Studies, 2011)
The importance of Zaydī sources for historical research on Muʿtazilī theology is generally acknowledged since the spectacular discoveries of unique manuscripts in Yemen in the 1950s. Yet the knowledge transfer and adoption of Muʿtazilī thought by the Yemeni Zaydiyya still remain an understudied field. Al-Ḥasan ar-Raṣṣāṣ (d. 1188) was one of the main promoters of Muʿtazilism in 6th/12th century Yemen. His works mainly focus on natural philosophy and include a systematic treatise on causality which is comprehensively examined and critically edited in this volume. The present study gives insight into a fascinating chapter of Islamic intellectual history and offers the first analysis of a Muʿtazilī theory of causality. Die Bedeutung zayditischer Quellen für die Erforschung muʿtazilitischer Theologie ist spätestens seit der spektakulären Wiederentdeckung einzigartiger Handschriften im Jemen der 1950er Jahre allgemein anerkannt. Dennoch sind der Wissenstransfer und die Adaption muʿtazilitischen Denkens durch die jemenitische Zaydiyya bislang kaum erforscht. Al-Ḥasan ar-Raṣṣāṣ (st. 1188) war einer der wichtigsten Protagonisten dieses Prozesses im Jemen des 6./12. Jahrhunderts. Unter seinen zahlreichen Schriften zu naturphilosophischen Fragen findet sich auch ein systematisches Traktat zur Kausalität, welches im vorliegenden Buch umfassend untersucht und kritisch ediert wird. Die Studie gewährt Einblick in ein faszinierendes Kapitel islamischer Geistesgeschichte und analysiert erstmals eine muʿtazilitische Systematik zur Kausalität.